Nutrient co‐limitation in the subtropical Northwest Pacific. Issue 1 (17th August 2021) - Browning, Thomas J.; Liu, Xin; Zhang, Ruifeng; Wen, Zuozhu; Liu, Jing; Zhou, Yaqian; Xu, Feipeng; Cai, Yihua; Zhou, Kuanbo; Cao, Zhimian; Zhu, Yuanli; Shi, Dalin; et al.
Abstract: Nutrients limiting phytoplankton growth in the ocean are a critical control on ocean productivity and can underpin predicted responses to climate change. The extensive western subtropical North Pacific is assumed to be under strong nitrogen limitation, but this is not well supported by experimental evidence. Here, we report the results of 14 factorial nitrogen–phosphorus–iron addition experiments through the Philippine Sea, which demonstrate a gradient from nitrogen limitation in the north to nitrogen–iron co‐limitation in the south. While nitrogen limited sites responded weakly to nutrient supply, co‐limited sites bloomed with up to 60‐fold increases in chlorophyll a biomass that was dominated by initially undetectable diatoms. The transition in limiting nutrients and phytoplankton growth capacity was driven by a gradient in deep water nutrient supply, which was undetectable in surface concentration fields. We hypothesize that this large‐scale phytoplankton response gradient is both climate sensitive and potentially important for regulating the distribution of predatory fish.